EVALUATION ON THE THERAPY APPROPRIATENESS AND ANTIHYPERTENSIVE AGENT SIDE EFFECTS TOWARD TYPE 2 DIABETES MELLITUS WITH CHRONIC KIDNEY DISEASE PATIENTS RECEIVING REGULAR HAEMODIALYSIS AT RSU PKU MUHAMMADIYAH YOGYAKARTA - Fef Rukminingsih; Djoko Wahyono; I Dewa Putu Pramantara (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice))
Antihypertensive selection accuracy determines the achievement of therapy target toward type 2 diabetes mellituswith chronic kidney disease patients who received regular hemodialysis treatment. The use of drugs in a longtimepotentially causes side effects and drug interactions as well.This research employed prospective observation by evaluating the appropriateness of therapy and monitoringdirectly the side effects of antihypertensive agent used toward type 2 diabetes mellitus with chronic kidney diseasepatients who received regular haemodialysis treatment at RSU PKU Muhammadiyah Yogyakarta during February– April 2011.For 42 patients having type 2 diabetes mellitus with chronic kidney disease who received regular haemodialysis treatment, it was found that patients who received appropriate therapy and achieved blood pressure therapy target was none, 4 patients (9.53%) received appropriate therapy yet the blood pressure remained uncontrolled, 2 patients(4.76%) received inappropriate therapy yet achieved controlled blood pressure and 36 patients (85.71%) receivedinappropriate therapy with remained uncontrolled blood pressure. From 42 patients, it was found that there were 11patients (26,20%) were possible and 5 patients (11,90%) were probable suffered from dry cough, 26 patients (61.91%) were possible for suffered from dizziness, 39 patients (92.86%) were possible suffered from headache, 2 patients (4.76%) were potentially suffered from fatigue and 13 patients (30,95%) were possible and 2 patients (4,76%) wereprobable suffered from drowsiness. Keywords: antihypertensive, type 2 diabetes mellitus, haemodialysis